THE MANAGEMENT ACCOUNTING TOOLS AND THE INTEGRATED REPORTING - Gabriel JINGA; Mădălina DUMITRU (SEA: Practical Application of Science, 2015)

(untitled)
During the recent years the stakeholders are asking for other pieces of information to be published along with the financial one, such as risk reporting, intangibles, social and environmental accounting. The type of corporate reporting which incorporates the elements enumerated above is the integrated reporting. In this article, we argue that the information disclosed in the integrated reports is prepared by the management accounting, not only by the financial accounting. Thus, we search for the management accounting tools which are used by the companies which prepare integrated reports. In order to do this, we analytically reviewed all the reports available on the website of a selected company. Our results show that the company is using most of the management accounting tools mentioned in the literature review part.